A RARE CASE OF METASTATIC PHEOCHROMOCYTOMA IN MULTIPLE ENDOCRINE NEOPLASIA TYPE 2A (MEN 2A) - Seng, Chiew Ken; Velaiutham, Shanty; Hui, Khaw Chong (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION In MEN 2A, there is a heritable predisposition to medullary thyroid carcinoma (MTC), pheochromocytoma and hyperparathyroidism. MEN2A-associated pheochromocytoma is typically benign. We report a case of malignant pheochromocytoma in MEN2A. METHODOLOGY A 45-year-old female was diagnosed with MEN 2A when she was 19-years-old as part of a family screening in the year 1996. Genetic analysis revealed a mutation in codon 634 of the RET proto-oncogene (cysteine-to-tyrosine substitution, C634Y). She underwent total thyroidectomy for MTC and bilateral adrenalectomy for bilateral pheochromocytoma in 1997. She developed recurrence of her pheochromocytoma and underwent laparoscopic left adrenalectomy in 2005. At that time, she also developed primary hyperparathyroidism and underwent total parathyroidectomy. However, her urinary catecholamines remained elevated. Iodine-131 meta-iodobenzylguanidine (I-131 MIBG) scan in 2007 revealed increased uptake in her left adrenal, liver, mediastinum, skull and upper abdomen. Since she was asymptomatic, she declined systemic therapy. Her disease subsequently progressed. She now experiences daily paroxysms with rising levels of urine metanephrines/normetanephrines. Latest 131-MIBG and Gallium-68 PET/CT scans showed progression with disease activity at her left adrenal bed and with regional node involvement and metastasis to lung, liver and bones. She is now agreeable for further therapy. RESULTS In patients with RET codon 634 mutations, pheochromocytoma occurs in 52% by the age of 50 years old. It is almost always benign. Metastatic pheochromocytoma in MEN2A is rare. Case series suggest a prevalence of 3-5%, in contrast to the prevalence of more than 10% in sporadic pheochromocytomas. CONCLUSION While MTC is the usual culprit of metastatic disease in MEN2A, it may rarely be due to malignant pheochromocytoma. Multidisciplinary approach to management is optimal.